PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA SISWA KELAS 3 TEMA 1 MATERI MEMAHAMI ARTI GAMBAR PADA LAMBANG NEGARA “GARUDA PANCASILA” - Safitri, Yosie; Marantika, Yuliana; Harjanto, Ambyah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
The purpose of this research is to develop multimedia products as alternative media in learning in elementary schools. This research is a research and development or Research and Development (R&D). Borg and Gall. The result of this research is a learning video for grade 3 theme 1 Understand the meaning of the image on the symbol of the Garuda Pancasila state. The conclusion of this study is important for teachers to have technological literacy to develop multimedia as a learning support so that students are able to understand the material properly and correctly so as to improve the results of students' cognitive and applications in daily life. The suggestion from this research is that the products produced must go through validation and trial before they are used or applied to students.